Fitocenološka analiza gozdne vegetacije na nahajališčih nekdanjih žgalnic živosrebrove rude v okolici Idrije - Dakskobler, Igor (Gozdarski vestnik, 2016)
We performed a phytosociological analysis of vegetation on six localities of former mercury ore burning sites in the forests in the surroundings of Idrija. We classify the inventorized stands into the following syntaxa: Galio rotundifolii-Abieteum, Omphalodo-Fagetum blechnetosum, Omphalodo-Fagetum aceretosum and Luzulo-Fagetum abietetosum. Within them, we determined 147 vascular plants (pteridophytes and spermatophytes), 97 (66 %) of which are attributed resilience to heavy metals in the soil by botanists. Species structure of the determined communities confirms the assumption, that the former burning sites are still a major source of pollution of the environment with mercury, but it is not directly connected with this pollution. We assume that in the process of secondary succession on the altered soil of the former burning sites above all the species, characteristic for sites on the mixed geological bedrock, where the soil in the valleys is rather moist and quite acid on the bulged, elevated parts, gradually prevailed.
Keywords: phytosociology; fitocenologija; fitoindikacije; žgalnice živosrebrove rude; Idrija; rudniki; rudniki živega srebra; Slovenia; Slovenija